Study of Navruz Folklore - Munis Juraeva Yunusovna (Researchparks Publishing, 2022)
Navruz is one of the rare monuments of the artistic thinking of our ancient ancestors and is considered an intangible cultural heritage that has been continuously developing over the centuries. This article describes the study of Navruz by the Uzbek folklorist M. Juraev, who studied national values and traditions of the national holiday Navruz.